The symbolic semantics of the typographical image in the designs of the cinematic poster (Journal of the College of Basic Education, 2022)
The poster is considered one of the most important means of communication with its intellectual and aesthetic contents, through which it aims to spread a specific idea, and based on the system of expressing the goal and the aesthetic features of the poster as one of the most difficult arts that present an effective goal as a result of its design, and the designer expresses the connotations and symbols within the poster and their cohesion With each other, generating inferences to embody communication ideas, in a manner that serves the poster positively and achieves direct contact for the recipient, as symbols play a major role in conveying modern technical developments that have swept the world at the present time, especially since the poster is one of the means of visual communication and has an effect in simulating the vision of the receiver with that. Symbols and semantics that have cognitive constants